Characteristics of Villagers' Spontaneous Repair and its Impact on the Conservation and Utilization of Traditional Residences in Zhejiang Traditional Villages - Yixuan Chen; Sishen Wang; Qiyu Cao; Wenqing Gao (Journal of Asian Architecture and Building Engineering, 2025)
In Zhejiang traditional villages, the villagers’ spontaneous repairing activities are frequent, while its characters and impacts remain to be explored. Based on an investigation of 131 traditional residences in 9 sample villages, the study finds that the roofs and doors are the most frequently repaired components, next is wall and wooden column. The repair funds mainly come from the residents. Additionally, the storage and unused residential spaces are increasing, and the infrastructure is gradually becoming more complete. However, installing air conditioning remains a challenge. Based on cluster analysis, villagers’ spontaneous repair behaviors can be classified into three types: neither conserved nor utilized (type 1), well conserved & utilized (type 2), and utilized but not conserved (type 3). Type 1 residents lack repair interest and funds, which leads to the damage of residences. Type 2 residents actively learn repair techniques and promote the long-term conservation of traditional residences. Type 3 repairs emphasize functionality and comfort, rather than preserving residence. The study points out two potential hazards: insufficient inter-generational inheritance and poor repair effects. Two proposals, integrating modern functions while conserving through professional design and technical support, promoting the development of tourism through the restoration, are put forward for further improvement.